Rootstock effects on growth and fruit composition of low‐yielding winegrape cultivars grown in a hot Australian climate. (5th December 2021) - Clingeleffer, P.R.; Kerridge, G.H.; Rühl, E.H.
Abstract: Background and Aims: The use of rootstocks to enhance the performance of low‐yielding wine cultivars grown under hot irrigated conditions was studied. Methods and Results: Field performance and grape composition of low‐vigour cultivars (Chasselas, Egiodola, Ehrenfelser, Gamay, Perdea, Reichensteiner and Roussanne) grown as own roots or grafted on rootstocks (1103 Paulsen, Dog Ridge, Ramsey, Schwarzmann and SO4) were assessed over three seasons. Across all cultivars, yield of own roots, SO4 and Schwarzmann was similar. Ramsey and 1103 Paulsen produced a higher yield without a major effect on juice composition. Dog Ridge produced excessive vigour and poor grape composition. Across the scion–rootstock combinations, high vine vigour, yield and berry mass were associated with high juice pH, K + and malic acid and low tartaric acid. Rootstock effects on juice K +, tartaric and malic acid were stable and independent of the scion cultivar. Conclusions: The performance of low‐vigour cultivars was enhanced by grafting on 1103 Paulsen and Ramsey. 'Scion conferred root vigour' was found under field conditions. Significance of the Study: The genetic diversity of cultivars available for wine production can be broadened by adoption of rootstocks for low‐vigour cultivars. Rootstock selection requires knowledge of inherent scion vigour and conferred rootstock vigour.